2019
DOI: 10.3390/su11216111
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Cognitive Congruence between Managers and Team Members’ Perceptions of Cooperation at Work

Abstract: Much of the research on the psychological dynamics of performance teams suffers from the following limitations: consideration of only one theoretical framework and analysis of just one perspective (e.g., manager–coach or team member). To address these shortcomings, this study used a Global Cooperation concept that synthesized five psychological frameworks: coordination, cohesion, cooperation, integration, and identification. The objective of this study was to examine the level of congruence–symmetry between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The results of the present study suggest that it is important to emphasize the need to continue promoting cooperation within teams, which could result in an increase in player motivation and a decrease in anxiety. On the other hand, an intervention on Team Building, as has been recommended [10,16] and applied [17], could help promote the improvement of team dynamics (mainly) and the other variables in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study suggest that it is important to emphasize the need to continue promoting cooperation within teams, which could result in an increase in player motivation and a decrease in anxiety. On the other hand, an intervention on Team Building, as has been recommended [10,16] and applied [17], could help promote the improvement of team dynamics (mainly) and the other variables in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There is research that has used this new psychological approach from the organizational level [16] and sports [17,18] in which it has been found that there are differences when the athlete is perceived from his role within the team (team member's point of view) and when it is perceived from a different role (coach's point of view).…”
Section: Introductionmentioning
confidence: 99%
“…The process is prioritized above the result of competitions, emphasizing individual growth and effort over final performance or rivalry with other athletes (Weiss, 1992). The importance of the interaction between coaches and team members and how this relationship is perceived is highlighted in recent research (García-Mas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the psychological variables that may affect the performance of sports teams has a long tradition in sports psychology, with key concepts such as sports cohesion (Carron and Brawley, 2000) and cooperation (Garcia-Mas et al, 2006), in addition to recent developments in the synthesis of the currently existing different conceptual frameworks addressed to explain psychological dynamics of the team, e.g., coordination, identification, collective efficacy, or integration (Garcia-Mas et al, 2019). Despite these attempts to clarify the psychological variables responsible for team dynamics, often other basic variables, such as group size, hierarchy, conformity, or social laziness are not considered as relevant either theoretically or practically.…”
Section: Introductionmentioning
confidence: 99%